(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background : Anticholinergic drugs are recommended as first line with Oxybutynin (IR) being one of the most commonly recommended drug. Older pharmacological agent such as propanthelene, dicyclomine and tricyclic antidepressent like imipramine have been used but have become alternative due to poor patient tolerability and lack of strong evidence from clinical trials. A combination of behavioral therapy and drug therapy has been shown to be more effective than either drug therapy or behavioral therapy alone. To assess the efficacy of Oxybutynin (IR) on number of micturition per day, episodes of incontinence per day and voided urinary volume along with the adverse effects of Oxybutynin (IR) and safety of the drug. Materials and methods: This study was conducted at the Department of Urology, Chittagong Medical College Hospital, Chittagong, from July, 2012 to June, 2013. Purposive sampling was done. Bladder diary was used for evaluating the symptoms of the patient during baseline and 08 weeks follow up. Perceived level of benefit of the patients was assessed and graded using Likert scale. Data analysis was conducted by SPSS version-21. Results: Out of 84 patients, 25 (29.8%) were male and 59 (70.2%) were female. Male female ratio was 1:2.4. The study revealed that the most of the patients, 49 (58.33%) were subjected to much benefit followed by 26 (30.95%) patients experienced little benefit and 09 (10.71%) patients were not benefited from the treatment. Conclusion: Oxybutynin showed a significant level of efficacy on overactive bladder with an acceptable level of side effects. JCMCTA 2018 ; 29 (1) : 23-27